Integration of Behavioral Frequency and Intention Information in Young Children's Trait Attributions. Issue 1 (1st November 2012) - Boseovski, Janet J.; Chiu, Korinne; Marcovitch, Stuart
Abstract Two experiments examined three‐ to six‐year‐olds' use of frequency and intention information to make trait attributions and behavioral predictions. In experiment 1, participants were told a story about an actor who behaved positively once or four times on purpose or incidentally. Children were most likely to make trait‐consistent behavioral predictions after hearing about several positive, intentional behaviors. Trait attributions were largely positive. Experiment 2 examined children's use of the same cues concerning negative behavioral outcomes. Participants tended to predict that actors who engaged in negative behavior would do so again, irrespective of intention, although younger children required more exemplars than older children. Participants were most likely to make negative trait attributions after hearing about multiple intentional behaviors; however, there was reluctance with age to describe actors as mean. Implications for children's 'theory of personality' are discussed.